Étienne Cabet e l'educazione in Icaria - Paolo Levrero (Firenze University Press, 2017)
According to the etymological and philological meaning given to the concept of utopia by the history of literature, philosophy and pedagogy, the article considers utopia as a criticism of the existing and a foreshadowing of a possible reality. The reference to a social order, marked by both the need for justice and the human inner harmony, is recognizable in the book Voyage en Icarie, the novel written by the French politician and reformer Étienne Cabet a few decades since the Revolution of the year 1789.